Is "No Response" on Diagnostic Auditory Brainstem Response Testing an Indication for Cochlear Implantation in Children?. Issue 1 (January 2015) - Hang, Anna X.; Roush, Patricia A.; Teagle, Holly F. B.; Zdanski, Carlton; Pillsbury, Harold C.; Adunka, Oliver F.; Buchman, Craig A.
<x xml:space="preserve">Abstract</x> Objectives: To compare the results of a "no response" (NR) result on auditory brainstem response (ABR) testing with those of behavioral pure-tone audiometry and ultimate clinical tracking to cochlear implantation (CI). Design: Retrospective review of pediatric patients who underwent multifrequency ABR testing in a 5 year span. Total of 1143 pediatric patients underwent ABR testing during the study period and 105 (9.2%) were identified with bilateral NR based on absent responses to both click and tone burst stimuli. For the children with NR, various clinical parameters were evaluated as these children progressed through the CI evaluation process. Children were grouped based on whether they underwent ABRs for diagnostic or for confirmatory purposes. Results: Of the 105 children who met inclusion criteria, 94 had sufficient follow-up to be included in this analysis. Ninety-one (96.8%) of 94 children with bilateral NR ABRs were ultimately recommended for and received a CI. Three (3.2%) children were not recommended for implantation based on the presence of multiple comorbidities rather than auditory factors. None of the children (0%) had enough usable residual hearing to preclude CI. For those who had diagnostic ABRs, the average time at ABR testing was 5.4 months (SD 6.2, range 1–36) and the average time from ABR to CI was 10.78 months (SD 5.0, range 3–38). Conclusions: CI should tentatively be recommended for children with a bilateral NR result with multifrequency ABR, assuming confirmatory results with behavioral audiometric testing. Amplification trials, counseling, and auditory-based intervention therapy should commence but not delay surgical intervention, as it does not appear to change the eventual clinical course. Children not appropriate for this "fast-tracking" to implantation might include those with significant comorbidities, auditory neuropathy spectrum disorder, and unreliable or poorly correlated results on behavioral audiometric testing.